ART MOVING ALONG THE PATH OF PROGRESS BY COMBINING RHYTHM STEP BY STEP: कदम से कदम ताल मिलाकर प्रगति के पथ पर साथ चलती कलाएँ - Chauhan, Manorama (International Journal of Research -GRANTHAALAYAH, 2015)
“The first and direct relation of beauty is the experience of the eyes. When man first opened his eyes, he found himself in the lap of nature. Natural beauty was scattered all around. Water, waterfalls, animals and birds tweet, sheets covered Hari-Hari Vasundhara. Humans took inspiration from this natural beauty, decorated the birds and the flowing waterfalls, the sweet music of the air, and the dancing of the animals with a gentle gesture. With this inspiration, humans continued to expand civilization with arts. Today, it is on the path of progress with many new experiments through the thought of mankind, and expression through inspiration. ” “सौन्दर्य का पहला और सीधा सम्बन्ध आखों द्वारा किया जाने वाला अनुभव है। सर्वप्रथम जब मानव ने अपनी आँखें खोली तो उसने अपने आप को प्रकृति की गोद में पाया। चहुँ ओर प्राकृतिक सौन्दर्य बिखरा हुआ था। पानी, झरने, पशु-पक्षियों का कलरव, चादर ओढ़े हरि-हरि वसुन्धरा। मानव ने इसी प्राकृतिक सौन्दर्य से प्रेरणा ग्रहण की, पक्षियों और कल-कल बहते झरने, हवा का मधुर संगीत, पशुओं के शारिरीक हाव भाव से नृत्य का रसास्वादन किया। इसी प्रेरणा के सहारे मानव, सभ्यता का कलाओं के साथ विस्तार करता गया। आज यह प्रेरणा के सहारे मानवमन की सूज बूझ, एवं अभिव्यक्ति के माध्यम से कई नये प्रयोगों के साथ प्रगति के पथ पर अग्रसर है।”